2018
DOI: 10.1108/jta-02-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and mobile devices: provenance of academic research through a bibliometric study

Abstract: Purpose This paper aims to outline a map of all the research that exists on mobile technology and tourism archived in the two main databases worldwide (Web of Science and Scopus). Accordingly, with the identification of all the scientific articles that deal with both mobile technology and tourism, the authors seek to ascertain the evolution of mobile technology in the tourism sector through the years, countries, universities and authors and determine the various collaborations brought about between authors, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…To validate our research topic on "digital tourism," we screened databases to check the exclusivity of this topic. We found bibliometric studies related to the use of new data analysis techniques (Palomoa et al, 2017), mobile devices (Ortega-Fraile et al, 2018), mobile technology (Chen et al, 2020), social media (Mehraliyev et al, 2019;Nusair et al, 2019), and innovation (Corte et al, 2019;Durán-Sánchez et al, 2019) in tourism. We also observed articles related to sustainability (Serrano et al, 2019) and smart tourism (Bastidas-Manzano et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate our research topic on "digital tourism," we screened databases to check the exclusivity of this topic. We found bibliometric studies related to the use of new data analysis techniques (Palomoa et al, 2017), mobile devices (Ortega-Fraile et al, 2018), mobile technology (Chen et al, 2020), social media (Mehraliyev et al, 2019;Nusair et al, 2019), and innovation (Corte et al, 2019;Durán-Sánchez et al, 2019) in tourism. We also observed articles related to sustainability (Serrano et al, 2019) and smart tourism (Bastidas-Manzano et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Palomoa et al (2017), presented how tourism research is making use of new data techniques like structural equation modeling, big data, and data mining over two decades. On the other hand, few studies determined the evolution of mobile technologies in the tourism industry over the years (Chen et al, 2020;Ortega-Fraile et al, 2018). We found studies related to social media in tourism and hospitality where researchers presented the social structure of collaborative networks (Mehraliyev et al, 2019) or systematic literature review (Nusair et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to physical interactions, virtual exploration is now also included in natural exploration, thanks to the development of technology. The use of computer-generated imagery (CGI), interactive videos (IR), virtual reality (IR), and augmented reality (AR) have the potential to provide new and innovative ways for students to engage in various virtual natural explorations [16][17][18][19]. It is suggested that exploration can help cultivate perceptions of social connectedness, empathy, and prosocial behaviors [20,21].…”
Section: Introductionmentioning
confidence: 99%